Thrombin generation and activated protein C resistance in the absence of factor V Leiden correlates with the risk of recurrent venous thromboembolism in women aged 18–65 years - Sonnevi, Kristina; Tchaikovski, Svetlana N.; Holmström, Margareta; Rosing, Jan; Bremme, Katarina; Lärfars, Gerd (Thrombosis and Haemostasis, 2011)
Identification of patients at high risk of recurrence after a first event of venous thromboembolism (VTE) remains difficult. Resistance to activated protein C (APC) is a known risk factor for VTE, but data on the risk of recurrence is controversial. We wanted to investigate whether APC resistance in the absence of factor V Leiden, determined with global coagulation test such as the thrombin generation assay, could be used as a marker for increased risk of recurrent VTE among women 18–65 years old after a first event of VTE. In a cohort of 243 women with a first event of VTE, plasma was collected after discontinuation of anticoagulant treatment and the patients were followed up for 46 months (median). Thrombin generation was measured via calibrated automated thrombography, at 1 pM and 10 pM of tissue factor (TF). In women without factor V Leiden (n=117), samples were analysed in the absence and in the presence of APC. Increase in ETP (endogenous thrombin potential) and peak height analysed in the presence of APC correlated significantly with higher risk of recurrence. At 1 pM, peak height correlated with increased risk of recurrence. In conclusion, high thrombin generation in the presence of APC, in women after a first event of VTE is indicative for an increased risk of a recurrence. We also found that thrombin generation at low TF (1 pM) is correlated with the risk of recurrence. Our data suggest that APC resistance in the absence of factor V Leiden is a risk factor for recurrent VTE.
Keywords: APC-resistance; thrombin generation; venous thrombosis; recurrence; women